Micro Technique for Determination of Nitrite in Water - Mir, S.A. (Asian Journal of Chemistry, 2016)
A new micro technique for determination of nitrite in water has been standardized. Potassium ferrocyanide (1.2 mg mL–1) forms a pale-green colour with nitrite (0.2 to 1.0 ppm) in presence of dilute HCl (12%). The colour reaches to peak intensity at 90 min and is stable for at least up to 150 min following acidification. The colour is monitored at 430 nm, is linear over the test range with regression estimate in units of absorbance value per μg total nitrite, b ± S.E. as 0.091 ± 0.002 (n = 30). Metallic ions (Zn, Cu, Mn, Cd, Fe) that interfere with the test are removed from the water sample with treatment of NaOH and the residual hydroxide ions removed by addition of MgCl2 solution. The extraction does not significantly affect nitrite recovery (P > 0.1). Nitrate ions do not interfere. The reaction is unlikely due to oxidation of ferrocyanide to ferricyanide by nitrous acid. The technique can be used as an alternative to the diazotization technique with advantage of requiring cost-effective reagents.